The maraviroc expanded access program — safety and efficacy data from an open-label study - Lazzarin, Adriano; Reynes, Jacques; Molina, Jean-Michel; Valluri, Srinivas; Mukwaya, Geoffrey; Heera, Jayvant; Craig, Charles; van der Ryst, Elna; Sierra-Madero, Juan G. (HIV Clinical Trials, 2015)
The maraviroc (MVC) expanded access program (EAP) was initiated to increase MVC availability to patients with limited treatment options. Darunavir (DRV), raltegravir (RAL), and etravirine (ETV) were either recently approved or under regulatory review at study initiation and available for coadministration with MVC. Thus, the safety of MVC in combination with new antiretroviral therapies (ARVs) could be assessed. This open-label safety study of MVC was conducted at 262 sites worldwide in 1032 R5 HIV-positive treatment-experienced patients with limited/no therapeutic options. Methods: Study visits included screening, baseline, end of study or early discontinuation, and follow-up 30 days after last dose. Interim visits for HIV-1 RNA and CD4 cell counts occurred according to local HIV infection management guidelines. Safety data were analyzed overall and by subgroup based on ARV combination [MVC+optimized background therapy (OBT), MVC ± OBT+DRV/r, MVC ± OBT+RAL, MVC ± OBT+RAL+DRV/r, MVC ± OBT+RAL+ETV ± DRV/r]. Results: Most (90.3%) adverse events (AEs) were of mild or moderate severity with few grade 3/4 events, discontinuations, or temporary discontinuations/dose reductions due to AEs or serious AEs. Similar results were observed across subgroups. Of treated patients, 79.9% and 50% had HIV-1 RNA < 400 copies/ml and < 50 copies/ml respectively, at the end of the study, early termination visits, or at last known status. Tropism changes and selection of MVC-resistant R5 virus, including high-level MVC dependence, were mechanisms of viral escape. Conclusion: MVC was well tolerated with virologic suppression observed in most patients.